Non-destructive evaluation of corrosion activity in reinforced concrete slab - Ismail, Mohammad (2008)
Nondestructive evaluation of corrosion of steel reinforcement in concrete due to ingress of chloride ions is intensively studied in a laboratory. Acoustic emission (AE) is used directly to estimate corrosion activity. Half-cell potential, polarization resistance and concrete resistivity are applied to evaluate corroded areas, compensating the potentials by the inverse boundary element method (IBEM). Embedded sensors attached to rebars are also employed to measure half-cell potential, polarization resistance and concrete resistivity in concrete. Results show that AE events are effectively associated with corrosion activity. It is noticed that no other techniques have managed to give an earlier warning of corrosion than AE technique. Half cell potential could locate the corroded areas in the concrete slab, while concrete resistivity and polarization resistance underestimate them. Embedded sensors are confirmed to be a promising tool for real-time monitoring for both corrosion activity and corrosion areas in reinforced concrete.